Facilitating international adaptation finance flows from private sources - Amrita Goldar; Somit Dasgupta; Sajal Jain; Diya Dasgupta; Poulomi Bhattacharya (Asian Development Bank Institute (ADBI), 2023)
Given its developmental underpinnings, adaptation finance has remained largely within the government purview of many developing countries. However, due to the exacerbation of climate impacts, there is a dire need to augment this source with private capital. This paper discusses the current landscape of adaptation financing, the role of the private sector, and the hurdles impinging on the finance flows from the said source. As a special case, it looks into the avenues available for climate risk adaptation, where the private sector contribution could be augmented through insurance and associated financial instruments for planned adaptation to climate risk. In addition, it makes a case for these financial instruments by looking at damage costs associated with unplanned impacts of climate-related natural calamities. Finally, analysis results from the investigation are then woven together as concrete suggestions for increasing private sector participation in adaptation financing in G20 countries.
Keywords: Q54; G150; G22; 330; G20; adaptation; climate finance